Cosmic Neutrino Background as a Ferromagnet - Gamboa-Rios, J; Lopez-Sarrion, J (Elsevier, 2014)
If cosmic background neutrinos interact very weakly with each other, through spin-spin interactions, then they may have experienced a phase transition, leading to a ferromagnetic ordering. The small magnetic field resulting from ferromagnetic ordering - if present before galaxy formation - could act as a primordial seed of the magnetic fields observed in several galaxies. Our findings suggest that the magnetization could occur in the right epoch, if the exchange boson of neutrino-neutrino interaction is a massless boson beyond the Standard Model, with a coupling constant of 2.2×10-13(m?10-4eV)2<g<2.3×10-7. The estimation of the magnetic seed is 2.3 × 10 -27 G ? BCNB ? 6.8 × 10 -10 G. © 2014 Elsevier B.V.